Design of a re-usable rocket for triggered-lightning experiments - Grant, Michael David (My University, 2007)
This dissertation presents the design of a re-usable rocket for use in triggered-lightning experiments. It is intended that the rocket will tow a thin wire to sufficient height so that the lightning mechanism will attach onto the wire and follow it to ground. The rocket design is inherently safe as it does not use explosive materials for its propulsion system, and hence conforms to South African explosive legislation. The designed rocket consists of a hybrid motor, which uses a solid combustion chamber and liquid oxidiser rather than solid motors which use a single solid fuel or a liquid motor which uses two liquid propellants. The mechanical performance of the oxidiser stage is critical in containing the pressurised oxidiser and regulating the flow of the oxidiser into the combustion chamber. The design of the combustion chamber and the rate at which the solid material burns is key to the generation of the pressure which is expelled through the nozzle to produce thrust. The design of the nozzle is covered in which the material from which it is made must withstand temperatures in excess of 1600 ◦C. The entire system was modelled to calculate the parameters of the various subsystems. The simulation study shows that the rocket will be able to reach 1 km with a complete section of wire towed behind it. A cost analysis, against other commercial rocket systems, was performed. The analysis concludes from the total cost of ownership that it is significantly cheaper to operate the designed rocket, over the course of the experiment, than other rocket systems.
Student Number : 0105159R - MSc(Eng) Dissertation - School of Electrical and Information Engineering - Faculty of Engineering and the Built Environment
Keywords: hybrid fuel; re-usable rocket; rocket design; total cost of ownership; triggered-lightning